Owen & Mzee : the true story of a remarkable friendship - Hatkoff, Isabella; Hatkoff, Craig; Kahumbu, P., (Paula); Greste, Peter (New York : Scholastic Press, 2006)
Illustrated text and full-color photographs tell the true story of the unusual relationship between Owen, a baby hippopotamus orphaned by the tsunami, and Mzee, a 130-year-old giant tortoise.
This book has been adapted from the original e-book, Owen and Mzee, which was first launched on the WNBC New York Five O'clock News as part of the Tribeca Film Festival.
Wilson's Children, October 2010.
School Library Journal starred, May 2006.
Notable/Best Books (A.L.A.), January 2007.
Book Links (A.L.A.), November 2006.
Pub Weekly, February 2006.
Keywords: Hippopotamus -- Behavior -- Kenya -- Juvenile literature; Aldabra tortoise -- Behavior -- Kenya -- Juvenile literature; Social behavior in animals -- Kenya -- Juvenile literature; Hippopotamus -- Behavior; Aldabra tortoise -- Behavior; Social behavior in animals; Animal behavior; Hippopotamus; Turtles; Tortoises; Animals -- Habits and behavior